ENGLISH VOCABULARY MATERIALS IN VOCATIONAL SCHOOL TEXTBOOK - Endang Estarina Situmorang (Universitas Suryakancana, 2020)
This research purpose is to investigate the compatibility of materials in the textbook Bahasa Inggris based on Tomlinson’s theory. The researchers use descriptive research as the type of the research. The data of the study are the content of English textbook entitled Bahasa Inggris SMA/SMK K-13. The analysis is done by using Three Level of Analysis by Little john (2011). They are: 1) Level 1 Analysis: ‘What is There’ (Objective Description), 2) Level 2 Analysis: ‘What is Required of Users’ (Subjective Analysis), and 3) Level 3 Analysis: ‘What is Implied’ (Subjective Inference). The result of this study shows that the English textbook Bahasa Inggris fulfills 15 criteria or 93,75% of Tomlinson’s theory. Therefore the textbook is suitable to be used by the students